(untitled) (Research, Society and Development, 2020)
This study aimed to evaluate the egg quality sold in several establishments in Imperatriz city Maranhão. It was used white shell eggs from commercial hen laying obtained according to the following treatments: open street markets, grocery stores, and supermarkets. For each treatment were obtained at three different local sales of eggs, which were chosen to cover different areas of the city. The variables studied were: egg weight, Haugh Units, yolk color, yolk, albumen and shell percentages, and yolk and albumen pH. The establishments type of egg sale did not influence the Haugh units, yolk color, and yolk pH. However, there was an influence on the egg weight, yolk, albumen, and shell percentage, as well as on albumen pH. Thus, eggs sold in open street markets had a higher weight (60.48 g) and the lowest shell percentage (9.23%). The eggs sold in supermarkets had a lower yolk percentage and higher albumen percentage when compared to egg grocery stores, and both had similar albumen percentage to the eggs sold in open street markets. For albumen pH, the eggs sold in supermarkets had the lowest value (9.18). In general, the eggs sold in open street markets, grocery stores, and supermarkets of the Imperatriz city had inferior quality due to low values of Haugh units obtained. However, taking into account the lowest albumen pH obtained for eggs of supermarkets, this establishment had better egg quality when compared to eggs sold in open street markets and grocery stores.